The reality of Arab universities benefiting from information services provided via the Internet for distance education programs | واقع إفادة الجامعات العربية من خدمات المعلومات المقدمة عبر شبكة الإنترنت لبرامج التعليم عن بُعد - AlZamil | الزامل, Mansour bin Abdullah | منصور بن عبدالله; Abdullah | عبد الله, Zainab Muhammad | زينب محمد; Al Rashid | الرشيد, Mohamed | محمد; Hopper | هوبر, Charles | شارل; Shehata | شحاتة, Hassan | حسن; Al Hagrasi | الهجرسي, Saad | سعد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
This study showed the reality of Arab public universities benefiting from information services provided via the Internet for distance education programs. The study reached the following results: -The extent of public universities in Arab countries’ adoption of distance education using the Internet:** It was found that only four Arab public universities have distance education programs via the Internet. -The extent to which universities in Arab countries benefit from distance education via the Internet: ** It turns out that the benefit Arab universities benefit from distance education via the Internet is very modest and does not live up to aspirations due to the presence of four distance education programs adopted by Arab universities on the Internet. The extent to which distance education programs in public universities in Arab countries benefit from information services provided via the Internet: It was found that no Arab public university has reached the highest stage in the theory used for evaluation (the transformation stage). While King Abdulaziz University in the Kingdom of Saudi Arabia topped the Arab public universities, reaching an advanced (penultimate) stage, which is the operations stage. Based on these results, the study recommended the need for Arab public universities to adopt distance education systems, especially because of the benefit of these programs in accommodating the numbers of applicants that exceed the capabilities of the traditional programs of those universities, the quantitative and qualitative expansion of programs via the Internet, and the investment of their informational and educational services. The study also recommended the importance of conducting a similar study to compare distance education programs using the Internet in private Arab universities and those programs in public Arab universities. | بينت هذه الدراسة واقع إفادة الجامعات العربية الحكومية من خدمات المعلومات المقدمة عبر شبكة الإنترنت لبرامج التعليم عن بُعد. وقد توصلت الدراسة إلى النتائج التالية: -حجم تبني الجامعات الحكومية في الدول العربية للتعليم عن بُعد باستخدام الإنترنت:** تبين أن أربع جامعات حكومية عربية فقط لديها برامج للتعليم عن بُعد عبر الإنترنت. -مدى استفادة الجامعات في الدول العربية من التعليم عن بُعد عبر الإنترنت:** تبين أن استفادة الجامعات العربية من التعليم عن بُعد عبر الإنترنت هي استفادة متواضعة جداً ولا ترقى للتطلعات وذلك لوجود أربعة برامجٍ للتعليم عن بُعد تتبناها الجامعات العربية على شبكة الإنترنت. مدى استفادة برامج التعليم عن بُعد بالجامعات الحكومية في الدول العربية من خدمات المعلومات المقدمة عبر الإنترنت: تبين أن لم تصل أي جامعة حكومية عربية إلى أعلى مرحلة في النظرية المستخدمة للتقييم (مرحلة التحول). بينما تصدرت جامعة الملك عبدالعزيز بالمملكة العربية السعودية – الجامعات الحكومية العربية حيث وصلت إلى مرحلة متقدمة (ما قبل الأخيرة) وهي مرحلة العمليات. بناءً على هذه النتائج، أوصت الدراسة بضرورة تبني الجامعات الحكومية العربية لنظم التعليم عن بُعد، خصوصاً لما لتلك البرامج من فائدة في استيعاب أعداد المتقدمين التي تفوق قدرات البرامج التقليدية لتلك الجامعات والتوسع الكمي والكيفي في البرامج عبر شبكة الإنترنت واستثمار ما لديها من خدمات معلوماتية وتعليمية. كما أوصت الدراسة بأهمية إجراء دراسة مماثلة للمقارنة بين برامج التعليم عن بُعد باستخدام الإنترنت في الجامعات العربية الأهلية وبين تلك البرامج الموجودة في الجامعات العربية الحكومية.